2019
DOI: 10.1167/iovs.19-27195
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Blue Light at Night Ameliorates Metabolic Abnormalities by Controlling Circadian Rhythms

Abstract: PURPOSE. Light-emitting diodes that emit high-intensity blue light are associated with blue-light hazard. Here, we report that blue light disturbs circadian rhythms by interfering with the clock gene in the suprachiasmatic nucleus (SCN) and that suppression of blue light at night ameliorates metabolic abnormalities by controlling circadian rhythms. METHODS. C57BL/6J mice were exposed to 10-lux light for 30 minutes at Zeitgeber time 14 for light pulse with blue light or blue-light cut light to induce phase shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 38 publications
5
34
0
4
Order By: Relevance
“…Several studies in humans have shown that increased exposure to short-wavelength light in the evening suppresses melatonin secretion ( Cajochen et al, 2005 ; Chellappa et al, 2011 ; Lee et al, 2018 ), increases alertness at night ( Cajochen et al, 2005 ; Figueiro et al, 2009 ), and can affect sleep architecture as measured with electroencephalography ( Münch et al, 2006 ; Chellappa et al, 2013 ). In contrast, filtering out short wavelengths at night has been reported to increase melatonin levels and improve sleep efficacy, quality, and latency in humans ( Burkhart and Phelps, 2009 ; Ayaki et al, 2016 ; Ostrin et al, 2017 ; Nagai et al, 2019 ). Contrary to what we expected, monkeys reared in blue light exhibited lower activity during the first hour and greater activity during the final hour of the lights-off period compared to white and red light reared monkeys, suggesting shorter sleep latency and earlier wake-up time.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in humans have shown that increased exposure to short-wavelength light in the evening suppresses melatonin secretion ( Cajochen et al, 2005 ; Chellappa et al, 2011 ; Lee et al, 2018 ), increases alertness at night ( Cajochen et al, 2005 ; Figueiro et al, 2009 ), and can affect sleep architecture as measured with electroencephalography ( Münch et al, 2006 ; Chellappa et al, 2013 ). In contrast, filtering out short wavelengths at night has been reported to increase melatonin levels and improve sleep efficacy, quality, and latency in humans ( Burkhart and Phelps, 2009 ; Ayaki et al, 2016 ; Ostrin et al, 2017 ; Nagai et al, 2019 ). Contrary to what we expected, monkeys reared in blue light exhibited lower activity during the first hour and greater activity during the final hour of the lights-off period compared to white and red light reared monkeys, suggesting shorter sleep latency and earlier wake-up time.…”
Section: Discussionmentioning
confidence: 99%
“…The circadian rhythm is essential for regulating all aspects of physiology, such as blood sugar in the endocrine system and inflammatory cells in the immune system. [27][28][29][30] Studies show that changes in biological rhythms can affect the body's physiological activities. The PER3 gene has been proven to be one of the very important clock genes in the human body, and it can affect downstream physiological activity changes by regulating sleep rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…The circadian rhythm is essential for regulating all aspects of physiology, such as blood sugar in the endocrine system and inflammatory cells in the immune system 27‐30 . Studies show that changes in biological rhythms can affect the body's physiological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Most contemporary dental LED curing lights emit light between 430 and 480 nm, and the most damaging wavelengths of blue light to the retina are thought to be around 440 nm 69 . Exposure to blue light has also been reported to affect sleep patterns 25,70,71 . Although a 'blue light hazard' to the retina has not yet been shown to occur in humans, dental personnel may be both chronically and acutely exposed to much greater high levels of blue light than the general population.…”
Section: Blue Light Hazardmentioning
confidence: 99%